Magazine «Sholpan» and national issues (Herald of Journalism, 2019)
The authors of the article analyzed the problems, that were on the pages of the publication by drawing on scientific facts and paying attention to the history of the magazine «Sholpan», which was published in 1922 in Tashkent. During the analysis, it was proved that there were raised ational problems through sections of the journal: «politics-economy», «knowledge-literature». Thematic differences of the articles, published in these ections were identified, the authors of the journal raised the problems and tried to investigate them as national values. In the writings of scholars, who studied the history of journalism, there was given undisputed evidence to the assertion that the publishers of the magazine were «nationalists», «Alashordians», an analysis of the concept «nationalist», «alashorda» was made. The problems that arose on the pages of the magazine were indeed the historical truth of the time. In this regard, from the first days of the publication, the authors of the magazine dreamed of the independence of the nation. The author also in separate articles doesn’t overlook the moments of the threat of publication stopping of the magazine. Although the life of the magazine «Sholpan» wasn’t long, it influenced on the perception of the national spirit. We can say that in the 20th years of the 20th centuries, the best essays of Kazakh literature and Kazakh writers found their reflection in the magazine «Sholpan», the author writes about it with concrete examples. Of course, it is necessary to assess the political situation of the time and epoch in order to assess the activity of any publication. However, «Sholpan», in the minds of the young Kazakh intelligence, formed an idea about the future of the Kazakh people. That is why the authors of the article were of the opinion that the magazine «Sholpan» spoke on behalf of the people and was the pride of the Kazakh press.
Keywords: Alash, Sholpan, nation, magazine, politics, literature, culture.